2019
DOI: 10.1007/s00024-019-02091-w
|View full text |Cite
|
Sign up to set email alerts
|

A New Approximate Method for Quantifying Tsunami Maximum Inundation Height Probability

Abstract: Regional and global tsunami hazard analysis requires simplified and efficient methods for estimating the tsunami inundation height and its related uncertainty. One such approach is the amplification factor (AF) method. Amplification factors describe the relation between offshore wave height and the maximum inundation height, as predicted by linearized plane wave models employed for incident waves with different wave characteristics. In this study, a new amplification factor method is developed that takes into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 27 publications
(36 reference statements)
0
55
0
Order By: Relevance
“…This MIH distribution is generally well approximated by a lognormal distribution (see also Davies et al 2017). Glimsdal et al (2019) estimated the amplification factors as a function of the offshore wave period and polarity for the TSUMAPS-NEAM POIs in the Mediterranean. They also took into account the coastal bathymetry around each POI.…”
Section: Mean Annual Rates Of Tsunami Hazard Intensitymentioning
confidence: 89%
See 2 more Smart Citations
“…This MIH distribution is generally well approximated by a lognormal distribution (see also Davies et al 2017). Glimsdal et al (2019) estimated the amplification factors as a function of the offshore wave period and polarity for the TSUMAPS-NEAM POIs in the Mediterranean. They also took into account the coastal bathymetry around each POI.…”
Section: Mean Annual Rates Of Tsunami Hazard Intensitymentioning
confidence: 89%
“…As discussed by Løvholt et al (2013), the amplification factor method gives exact estimates for the MIH under the special condition of non-breaking plane waves, but this method also assumes incident plane waves and hence neglects local effects such as focusing and refraction. It was recently shown that the amplification factor applied to the offshore value at the POI provides a good and almost unbiased estimator of the median of the whole MIH distribution for a set of onshore transects over a coastline stretch of a few kilometers behind the POI (Glimsdal et al 2019). This MIH distribution is generally well approximated by a lognormal distribution (see also Davies et al 2017).…”
Section: Mean Annual Rates Of Tsunami Hazard Intensitymentioning
confidence: 99%
See 1 more Smart Citation
“…The suggested formula, which gives the best fit with the data of numerical simulations in general is      These results can also be used in tsunami forecast. Sometimes, in order to save time for tsunami forecast, especially for long distance wave propagation, the tsunami run-up height is not simulated directly, but estimated using analytical or empirical formulas (Glimsdal et al 2019;Løvholt et al 2012). In these cases we recommend using formulas, which take into account the face front wave steepness.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The numerical technique to simulate the wave run-up was described previously in Dutykh et al (2011a). The bathymetry source term is discretized using the hydrostatic reconstruction technique, which implies the well-balanced property of the numerical scheme (Gosse, 2013).…”
Section: Numerical Modelmentioning
confidence: 99%